Nordisk judaistik = Scandinavian Jewish studies - Sällskapet för judaistisk forskning (Sällskapet för judaistisk forskning, 1975)
Aims at promoting Jewish studies in Scandinavia by publishing scholarly articles, surveys and documents, by reviewing recent literature, and compiling bibliographies. The journal is multidisciplinary and welcomes articles from a vast range of research fields within which Jewish themes are analysed, e.g. history, the study of religions, linguistics, theology, anthropology, social sciences and the arts. The journal focuses on Jewish studies in Scandinavia and research conducted by scholars tied to Nordic universities. The contributions are published in one of the Scandinavian languages, or in English, German or French, with an abstract in English.--About the journal.
Keywords: Jews : History : Periodicals; Jews : Scandinavia : Periodicals; Jews; Scandinavia